2023
DOI: 10.1007/s10103-023-03855-6
|View full text |Cite
|
Sign up to set email alerts
|

Fractional CO2 laser versus 1064-nm long-pulsed Nd:YAG laser for inflammatory acne vulgaris treatment: a randomized clinical trial

Tasneem Muhammad Hammoda,
Naglaa Abdallah Ahmed,
Mervat Hamdino

Abstract: Acne vulgaris is challenging to treat for several individuals. Laser therapy may be a desirable alternative to traditional therapies with limited success. This study aimed to assess efficacy of fractional CO2 laser versus Nd:YAG laser for acne vulgaris therapy. Thirty cases with acne vulgaris underwent both fractional CO2 laser and Nd: YAG laser treatments in a randomized split face design at a 14-day interval for four sessions. The clinical efficacy was evaluated by counting acne lesions and utilizing the Glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…While laser wavelengths such as 532-, 585-and 595-, 1064-, and 1450-nm have been utilized in the treatment of AV, 12 they have not exhibited a clear preference for absorption by sebaceous glands over water, hemoglobin, or melanin. 18 In recent years, the application of 1726 nm laser has gained popularity in this context, operating on the principle of selective photothermolysis. 19,20 Studies have found that the 1726 nm wavelength displays a heightened propensity for preferential absorption by sebaceous glands, consequently leading to reduction in AV lesions.…”
Section: Discussionmentioning
confidence: 99%
“…While laser wavelengths such as 532-, 585-and 595-, 1064-, and 1450-nm have been utilized in the treatment of AV, 12 they have not exhibited a clear preference for absorption by sebaceous glands over water, hemoglobin, or melanin. 18 In recent years, the application of 1726 nm laser has gained popularity in this context, operating on the principle of selective photothermolysis. 19,20 Studies have found that the 1726 nm wavelength displays a heightened propensity for preferential absorption by sebaceous glands, consequently leading to reduction in AV lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The laser is similarly able to penetrate deeper into the skin when acting on skin tissue [1][2][3]. The study of the interaction mechanism between 1064 nm lasers and skin tissue is a very complex and wide-ranging topic in research areas [4][5][6][7][8][9] such as laser surgery, laser thermotherapy and laser imaging, which has become a difficult problem at the intersection of laser physics and biomedicine. This laser finds widespread employment in skin ailment therapy, with its impact on skin integrity forming a pivotal facet of laser-based biological investigations.…”
Section: Introductionmentioning
confidence: 99%